Irradiation method of helium plasma on lithiated graphite containing silicon carbide coating
By lithiating the silicon carbide-containing coating graphite and irradiating plasma, the interaction between helium plasma and lithiated silicon carbide-containing coating graphite is simulated and studied, which solves the problem that cannot be effectively simulated and studied in the prior art, and achieves an in-depth understanding and improvement of the plasma characteristics in the fusion reactor.
Patent Information
- Application Number
- CN202411735615.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-07
AI Technical Summary
The interaction between helium plasma and lithiated silicon carbide-containing coating graphite in the prior art cannot be effectively simulated, making it difficult to understand and improve the plasma characteristics in the fusion reactor.
By lithiating the silicon carbide-containing coating graphite, lithiated silicon carbide-containing coating graphite was obtained, and plasma cleaning and helium plasma irradiation were performed on this basis, and the interaction between helium plasma and lithiated silicon carbide-containing coating graphite was simulated and studied.
This method can effectively simulate and study the interaction between helium plasma and lithiated silicon carbide-containing coating graphite, helping to understand and improve plasma characteristics in fusion reactors.
Smart Images

Figure CN119571246A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plasma irradiation, in particular to a method for irradiating lithiated silicon carbide-containing coated graphite with helium plasma. Background Art
[0002] Carbon materials have low atomic coefficients, high melting points (4043°C), good thermal conductivity, small neutron absorption cross-sections, and can maintain their mechanical strength at high temperatures. They are selected as plasma-facing materials for magnetic confinement fusion reactors. However, because carbon atoms have a low sputtering threshold (0.78eV), sputtered carbon atoms will contaminate the core plasma. Silicon carbide coatings are used to protect graphite substrate materials in fusion reactors because silicon carbide has the advantages of stable refractory surface, high toughness, thermal shock resistance, low neutron activation energy, good chemical compatibility with graphite substrates, and similar thermal expansion coefficients. At the same time, because lithium has the advantages of absorbing impurity atoms and having good compatibility with core plasmas, it has been confirmed in EAST and D-III devices that lithium-doped graphite walls can effectively improve plasma characteristics.
[0003] So far, many research institutions at home and abroad have studied the interaction between lithiated graphite and plasma. JPAllain et al. studied the surface chemical properties of lithiated graphite substrate as a plasma-facing material for fusion reactors. The experimental results show that the lithium wall based on ATJ graphite will generate lithium peroxide and lithium carbonate when exposed to the atmospheric environment for a long time, and can absorb hydrogen in time, playing the role of "hydrogen pump". It is also found that lithiated graphite can reduce 10-30% of physical sputtering. CNTaylor et al. studied the physical and chemical properties of deuterium after retention on the surface of lithiated graphite. XPS experiments studied the effect of D irradiation on lithiated graphite. Compared with unlithiated graphite, the surface chemical properties of lithiated graphite changed dramatically after bombardment with D ions with an energy of 500eV. Many complex compounds were generated on the graphite surface instead of LiD under pure lithium. The XPS spectrum also showed that when the flux of D was between 3.8 and 5.2×10 17 cm 2When the Li-OD (533.0±0.6eV) and Li-CD (291.4±0.6eV) bonds begin to reach saturation. Michael E. Spahr et al. used differential electrochemical mass spectrometry to study the surface activity of graphite and passivation layer during the first electrochemical lithium injection process. The results showed that the structural ordering of graphite powder during the electrochemical lithium injection process would cause a layer of exfoliation on the graphite surface. H. Yagi et al. studied the interaction between plasma and ion beam and lithiated graphite. The experimental results showed that lithiated wall treatment would reduce the chemical sputtering of ions on graphite. When lithiated graphite was exposed to hydrogen, different methanes would be released, but they would gradually decrease. At the same time, XPS showed that when the temperature was below 500K, after the lithiated graphite was irradiated with hydrogen plasma, a large number of oxygen atoms existed on the surface, and the chemical sputtering was reduced. It can be seen that studying a method of irradiating lithiated silicon carbide-containing coated graphite with helium plasma is of great significance to simulate the interaction between helium plasma and lithiated silicon carbide-containing coated graphite. Summary of the invention
[0004] The object of the present invention is to provide a method for irradiating lithiated silicon carbide coated graphite with helium plasma, so as to solve the problem that the interaction between helium plasma and lithiated silicon carbide coated graphite cannot be simulated and studied in the prior art.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for irradiating lithiated silicon carbide-containing coated graphite with helium plasma, comprising the following steps:
[0007] (1) lithiation of silicon carbide-coated graphite to obtain lithiated silicon carbide-coated graphite;
[0008] (2) The lithiated silicon carbide-containing coated graphite is sequentially subjected to plasma cleaning and helium plasma irradiation.
[0009] Preferably, in step (1), the lithiation device is a high-temperature corrosion tank; the high-temperature corrosion tank comprises a tank body, a lid, a copper sealing ring, a copper gasket and a tungsten crucible.
[0010] Preferably, a cooling water channel is provided on the cover; the top end of the tank body has an edge portion, wherein the edge portion is located at the outer periphery of the top end of the tank body; and the edge portion is used to fix the cover.
[0011] Preferably, the lithiation step is:
[0012] S1. Place lithium in a tungsten crucible and then place it at the bottom of the tank;
[0013] S2. Fix the silicon carbide coated graphite on the copper gasket, then install the copper sealing ring and the copper gasket on the top of the tank body, and finally seal it with a lid to assemble a high temperature corrosion tank;
[0014] S3. Cooling water is introduced into the cooling water channel on the cover to heat the high-temperature corrosion tank to obtain lithiated silicon carbide-containing coated graphite.
[0015] Preferably, steps S1, S2 and S3 are carried out in an argon atmosphere; the temperature of the cooling water is 0-20°C; the heating temperature is 400-600°C, and the heating time is 1-3h.
[0016] Preferably, in step (2), the process parameters of plasma cleaning are: argon gas flow rate is 1500-2500sccm, discharge current is 80-120A, and magnetic field is 0.1-0.3T.
[0017] Preferably, in step (2), the process parameters of helium plasma irradiation are: bias voltage of 20-200 V, helium gas flow rate of 1000-5000 sccm, discharge current of 50-150 A, and magnetic field of 0.02-0.4 T.
[0018] Beneficial effects of the present invention:
[0019] The lithiation method of the present invention can control the lithiation thickness of the doped graphite surface to make the lithiation more uniform, control the deposition thickness of lithium, and accelerate the deposition rate of lithium through water cooling. The helium plasma irradiation method for lithiated silicon carbide coated graphite can simulate the interaction between helium plasma plasma and lithiated silicon carbide coated graphite in a fusion reactor. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the structure of the high temperature corrosion tank of the present invention, wherein 1-lid, 2-copper sealing ring, 3-copper gasket, 4-graphite containing silicon carbide coating, 5-tungsten crucible, 6-tank body;
[0021] Figure 2 A support for use in helium plasma irradiation according to the present invention, wherein 7 is a base, 8 is an insulating ceramic support, 9 is a bias baffle, 10 is a sample support, 11 is a lithiated silicon carbide-containing coated graphite, and 12 is a plasma beam;
[0022] Figure 3 This is a SEM image of the graphite containing silicon carbide coating used in Example 1, magnified 500 times;
[0023] Figure 4 This is a SEM image of the graphite containing silicon carbide coating used in Example 1, magnified 1000 times;
[0024] Figure 5This is a SEM image of the graphite containing silicon carbide coating used in Example 1, magnified 5000 times;
[0025] Figure 6 This is a SEM image of the irradiated lithiated silicon carbide-containing coated graphite of Example 1, magnified 500 times;
[0026] Figure 7 This is a SEM image of the irradiated lithiated silicon carbide-containing coated graphite of Example 1, magnified 1000 times;
[0027] Figure 8 This is a SEM image of the irradiated lithiated silicon carbide-containing coated graphite of Example 1, magnified 1000 times;
[0028] Fig. 9 This is a SEM image of the cross section of the lithiated silicon carbide-containing coating graphite after irradiation in Example 1;
[0029] Fig.10 This is a depth distribution diagram of different elements in the lithiated silicon carbide-coated graphite after irradiation in Example 1. DETAILED DESCRIPTION
[0030] The present invention provides a method for irradiating lithiated silicon carbide-containing coated graphite with helium plasma, comprising the following steps:
[0031] (1) lithiation of silicon carbide-coated graphite to obtain lithiated silicon carbide-coated graphite;
[0032] (2) The lithiated silicon carbide-containing coated graphite is sequentially subjected to plasma cleaning and helium plasma irradiation.
[0033] In the present invention, in the step (1), the lithiation device is a high-temperature corrosion tank; the high-temperature corrosion tank comprises a tank body, a cover, a copper sealing ring, a copper gasket and a tungsten crucible.
[0034] There is no particular limitation on the material of the can body and the cover in the present invention, as long as the material of the can body can withstand temperatures up to 1000° C. The material of the can body and the cover used in the embodiment of the present invention is 316L stainless steel.
[0035] The lid is provided with a cooling water channel; the top of the tank body has an edge portion, wherein the edge portion is located at the outer periphery of the top of the tank body; the edge portion is used to fix the lid. The cooling water channel is provided on the lid, on the one hand, to form a temperature gradient inside the tank body so that the evaporated lithium can be deposited in time when encountering low temperature; on the other hand, it is to prevent the copper sealing ring from deforming, because the optimal working temperature of the copper sealing ring is not more than 300°C. By passing cooling water, the temperature of the copper sealing ring can be prevented from being too high, and the copper sealing ring can be protected in a normal working state.
[0036] In the present invention, screw holes are provided on the cover and the edge portion for fixing the cover.
[0037] In the present invention, the inner diameter of the edge portion is equal to the outer diameter of the tank body, which is convenient for placing the copper sealing ring. Preferably, the edge portion is welded to the top of the tank body.
[0038] In the present invention, the outer diameter of the copper sealing ring is equal to the inner diameter of the edge, and the inner diameter is larger than the inner diameter of the can body; the diameter of the copper gasket is larger than the inner diameter of the can body and smaller than the inner diameter of the copper sealing ring, ensuring that the copper gasket is located at the top of the can body; the thickness of the copper sealing ring and the thickness of the copper gasket are the same as the thickness of the edge, ensuring that the copper sealing ring and the copper gasket are in full contact with the lid.
[0039] In the present invention, the lithiation step is:
[0040] S1. Place lithium in a tungsten crucible and then place it at the bottom of the tank;
[0041] S2. Fix the silicon carbide coated graphite on the copper gasket, then install the copper sealing ring and the copper gasket on the top of the tank body, and finally seal it with a lid to assemble a high temperature corrosion tank;
[0042] S3. Cooling water is introduced into the cooling water channel on the cover to heat the high-temperature corrosion tank to obtain lithiated silicon carbide-containing coated graphite.
[0043] In the present invention, the graphite containing silicon carbide coating is fixed on the copper washer, and there is no special limitation on the fixing method, as long as the graphite containing silicon carbide coating is ensured to be in full contact with the copper washer. In the embodiment of the present invention, screws are used for fixing.
[0044] In the present invention, steps S1, S2 and S3 are carried out in an argon atmosphere; the temperature of the cooling water is 0-20°C, preferably 10°C; the heating temperature is 400-600°C, preferably 500°C, and the heating time is 1-3h, preferably 2h.
[0045] In the present invention, preferably, the lithiated graphite containing silicon carbide coating is mounted on a bracket before plasma cleaning; the bracket comprises a movable base, an insulating ceramic bracket, a bias baffle, and a sample bracket; the insulating ceramic bracket is T-shaped; the insulating ceramic bracket is located on the movable base; the bias baffle is located at the top of the insulating ceramic bracket; the sample bracket is located at the front end of the bias baffle, and the lithiated surface of the lithiated graphite containing silicon carbide coating faces the plasma during irradiation. The structure of the bracket is as follows Figure 2 shown.
[0046] In the present invention, in step (2), the process parameters of plasma cleaning are: argon gas flow rate is 1500-2500sccm, preferably 1800-2200sccm; discharge current is 80-120A, preferably 90-110A, and more preferably 100A; magnetic field is 0.1-0.3T, preferably 0.2T.
[0047] In the present invention, plasma cleaning is first performed to clean a layer of lithium covering the surface of lithiated silicon carbide coated graphite. When the lithiated silicon carbide coated graphite is transferred from the vacuum glove box to the irradiation device, the lithium on the surface will react with oxygen, nitrogen and water vapor in the air. Cleaning is performed to remove impurities.
[0048] In the present invention, in the step (2), the process parameters of helium plasma irradiation are: bias voltage is 20-200V, preferably 30-150V, and more preferably 40-100V; helium flow rate is 1000-5000sccm, preferably 2000-4000sccm, and more preferably 2000-3000sccm; discharge current is 50-150A, preferably 70-130A, and more preferably 90-110A; magnetic field is 0.02-0.4T, preferably 0.05-0.3T, and more preferably 0.15-0.2T.
[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0050] The preparation method of the silicon carbide coating used in the embodiment of the present invention is as follows:
[0051] The SiC coating was prepared on the surface of graphite material by chemical vapor deposition. Specifically, the graphite was first cleaned with anhydrous ethanol by ultrasonic and dried in an oven, and then placed in a sintering furnace with good sealing. Then the sintering furnace was connected to the air inlet pipe and the gas mixing tank, H2 was used as the carrier gas and dilution gas, Ar was used as the protective gas, and trichloromethylsilane was used as the silicon source. The trichloromethylsilane was introduced into the reaction chamber by the bubbling method, and the heating rate and deposition temperature were controlled. The flow rate of trichloromethylsilane + H2 mixed gas and the flow rate of Ar were controlled respectively. After the temperature reached 1000°C, it was kept warm for 5 hours, and finally the SiC coating was prepared on the surface of the graphite substrate.
[0052] Example 1
[0053] In a vacuum glove box, lithium is placed in a tungsten crucible, and then placed at the bottom of a tank (the tank is made of 316L stainless steel); the silicon carbide coated graphite is fixed to the copper washer by screws, and then the copper washer is placed on the top of the tank, and then the copper sealing ring is placed. The tank has an edge portion, and the edge portion has the same thickness as the copper washer and the copper sealing ring. Screw holes are set on the edge portion and the lid, and the lid is fixed to the edge portion by bolts to seal the tank to assemble a high-temperature corrosion tank; cooling water (wherein the temperature of the cooling water is 10°C) is passed through the cooling water channel on the lid, and the high-temperature corrosion tank is heated at a temperature of 500°C for 2 hours to obtain lithiated silicon carbide coated graphite. The operation in the vacuum glove box is to ensure that all steps are carried out in an argon atmosphere.
[0054] Install the lithium-containing silicon carbide coated graphite on a bracket (the bracket structure is as follows Figure 2 The sample was placed on a sample holder (as shown in the figure), followed by plasma cleaning, with the following process parameters: argon flow rate of 2000sccm, discharge current of 100A, and magnetic field of 0.2T; finally, helium plasma irradiation was performed, with the following process parameters: bias voltage of 40V, helium flow rate of 2000sccm, discharge current of 90A, and magnetic field strength of 0.05T, to obtain irradiated lithiated silicon carbide coated graphite.
[0055] Example 2
[0056] In a vacuum glove box, lithium is placed in a tungsten crucible, and then placed at the bottom of a tank (the tank is made of 316L stainless steel); the silicon carbide coated graphite is fixed to the copper washer by screws, and then the copper washer is placed on the top of the tank, and then the copper sealing ring is placed. The tank has an edge portion, and the edge portion has the same thickness as the copper washer and the copper sealing ring. Screw holes are set on the edge portion and the lid, and the lid is fixed to the edge portion by bolts to seal the tank to assemble a high-temperature corrosion tank; cooling water (wherein the temperature of the cooling water is 10°C) is passed through the cooling water channel on the lid, and the high-temperature corrosion tank is heated at a temperature of 500°C for 2 hours to obtain lithiated silicon carbide coated graphite. The operation in the vacuum glove box is to ensure that all steps are carried out in an argon atmosphere.
[0057] Install the lithium-containing silicon carbide coated graphite on a bracket (the bracket structure is as follows Figure 2 The sample was placed on a sample holder (as shown in the figure), followed by plasma cleaning, with the following process parameters: argon flow rate of 1500sccm, discharge current of 90A, and magnetic field of 0.1T; finally, helium plasma irradiation was performed, with the following process parameters: bias voltage of 20V, helium flow rate of 3000sccm, discharge current of 110A, and magnetic field strength of 0.15T, to obtain irradiated lithiated silicon carbide coated graphite.
[0058] Example 3
[0059] In a vacuum glove box, lithium is placed in a tungsten crucible, and then placed at the bottom of a tank (the tank is made of 316L stainless steel); the silicon carbide coated graphite is fixed to the copper washer by screws, and then the copper washer is placed on the top of the tank, and then the copper sealing ring is placed. The tank has an edge portion, and the edge portion has the same thickness as the copper washer and the copper sealing ring. Screw holes are set on the edge portion and the lid, and the lid is fixed to the edge portion by bolts to seal the tank to assemble a high-temperature corrosion tank; cooling water (wherein the temperature of the cooling water is 10°C) is passed through the cooling water channel on the lid, and the high-temperature corrosion tank is heated at a temperature of 500°C for 2 hours to obtain lithiated silicon carbide coated graphite. The operation in the vacuum glove box is to ensure that all steps are carried out in an argon atmosphere.
[0060] Install the lithium-containing silicon carbide coated graphite on a bracket (the bracket structure is as follows Figure 2 The sample was placed on a sample holder (as shown in the figure), followed by plasma cleaning, with the following process parameters: argon flow rate of 2500sccm, discharge current of 120A, and magnetic field of 0.3T; finally, helium plasma irradiation was performed, with the following process parameters: bias voltage of 100V, helium flow rate of 1000sccm, discharge current of 50A, and magnetic field strength of 0.3T, to obtain irradiated lithiated silicon carbide coated graphite.
[0061] The graphite containing silicon carbide coating and the irradiated lithiated graphite containing silicon carbide coating in Example 1 were analyzed by scanning electron microscopy and energy spectrum analysis, and the results are as follows:
[0062] Figures 3 to 5 The SEM images of graphite with silicon carbide coating at different magnifications are shown in Figure 2. Figures 6 to 8 The SEM images of lithiated graphite with silicon carbide coating after irradiation under different multiples of the method can be seen from the figure: the surface of graphite with silicon carbide coating is relatively flat, the grain size is relatively uniform, the size is about 10μm, the surface density is very good, and the SEM (x5000) image shows that the grains are polygons with smooth surfaces and sharp edges, and the layers between the grains are relatively clear, and the crystallinity is relatively good; the surface of lithiated graphite with silicon carbide coating after irradiation is uneven, the grain size is different, the size range is between 1 and 30μm, and the surface has fallen off, indicating that the plasma etching is more serious. From the SEM (x5000) image, it can be seen that the grains have two extremes of coarsening and refinement, and many fine particles are attached to the surface of large grains, and all large grains are adhered together, with poor crystallinity.
[0063] Fig. 9 This is a SEM image of the cross section of the lithiated silicon carbide-containing coated graphite after irradiation in Example 1. It can be seen that a loose layer with a thickness of about 50 μm appears, and it can also be seen that the surface of the sample is uneven after irradiation. Fig.10This is the depth analysis diagram of different elements of the lithiated silicon carbide-coated graphite after irradiation of Example 1. It can be seen that the silicon content gradually decreases with the increase of depth and finally tends to zero. When the depth is greater than 50μm, the silicon content drops to zero. The carbon content gradually increases with the increase of depth and finally tends to be stable. When the depth is greater than 50μm, the carbon content tends to be stable, that is, it reaches the depth of the substrate; because lithium has a very strong oxygen absorption ability, there is still a small amount of oxygen content in the sample, which gradually decreases with the increase of depth and finally tends to zero. When the depth is greater than 12μm, the oxygen content drops to zero. This is because silicon carbide will undergo a decomposition reaction in high-temperature liquid metal. Due to the action of plasma, the surface temperature of the sample rises. At the same time, under the action of plasma, the decomposition of silicon carbide will be accelerated. After the decomposition of silicon carbide, carbon and silicon atoms are formed. Compared with silicon atoms, carbon atoms have lower sputtering energy (0.78eV), so the plasma preferentially sputters carbon atoms, resulting in silicon enrichment. At the same time, a loose layer appears on the surface of silicon carbide under the corrosion of liquid lithium, resulting in severe surface etching.
[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for irradiating lithiated silicon carbide coated graphite with helium plasma, characterized in that: The steps include: (1) lithiation of the silicon carbide-coated graphite to obtain lithiated silicon carbide-coated graphite; (2) The lithiated silicon carbide-coated graphite is sequentially subjected to plasma cleaning and helium plasma irradiation.
2. The method for irradiating lithiated silicon carbide coated graphite with helium plasma according to claim 1, characterized in that: In the step (1), the lithiation device is a high-temperature corrosion tank; the high-temperature corrosion tank comprises a tank body, a lid, a copper sealing ring, a copper gasket and a tungsten crucible.
3. The method for irradiating lithiated silicon carbide coated graphite with helium plasma according to claim 2, characterized in that: A cooling water channel is arranged on the cover; the top end of the tank body has an edge portion, wherein the edge portion is located at the outer periphery of the top end of the tank body; and the edge portion is used to fix the cover.
4. The method for irradiating lithiated silicon carbide-containing coated graphite with helium plasma according to claim 2 or 3, characterized in that: The steps of the lithiation are: S1. Place lithium in a tungsten crucible and then place it at the bottom of the tank; S2. Fix the silicon carbide coated graphite on the copper gasket, then install the copper sealing ring and the copper gasket on the top of the tank body, and finally seal it with a lid to assemble a high temperature corrosion tank; S3. Cooling water is introduced into the cooling water channel on the cover to heat the high-temperature corrosion tank to obtain lithiated silicon carbide-containing coated graphite.
5. The method for irradiating lithiated silicon carbide coated graphite with helium plasma according to claim 4, characterized in that: The steps S1, S2 and S3 are carried out in an argon atmosphere; the temperature of the cooling water is 0-20°C; the heating temperature is 400-600°C, and the heating time is 1-3h.
6. The method for irradiating lithiated silicon carbide coated graphite with helium plasma according to claim 1, characterized in that: In the step (2), the process parameters of plasma cleaning are: argon gas flow rate is 1500-2500sccm, discharge current is 80-120A, and magnetic field is 0.1-0.3T.
7. The method for irradiating lithiated silicon carbide coated graphite with helium plasma according to claim 6, characterized in that: In the step (2), the process parameters of helium plasma irradiation are: bias voltage of 20-200V, helium gas flow rate of 1000-5000sccm, discharge current of 50-150A, and magnetic field of 0.02-0.4T.